UI Greenmetric World University Rankings 2024 - UiTM, UGC (UiTM Green Centre, 2024)
Universiti Teknologi MARA (UiTM) has steadily climbed the UI Greenmetric World University Rankings 2024, securing 107th position globally and 6th among Malaysian institutions. This milestone reflects UiTM’S ongoing commitment to sustainability since joining the rankings in 2019, marking six consecutive years of improvement.